Preferensi Mahasiswa dalam Pemilihan Hunian Sewa di Kecamatan Depok, Sleman, Yogyakarta - Michon Pra Marchviano Barataman, Dibertia (ReTII, 2024)
The demand for temporary housing for students in Yogyakarta, particularly in Depok District, has increased along with the growing number of incoming students. This study aims to identify students’ preferences in choosing rental housing, which is part of the studentification phenomenon in Depok District. The research method used is descriptive quantitative, with questionnaires as the data collection instrument. The primary factors identified as determinants are price, proximity to campus, adequate facilities, and aspects of safety and environmental comfort. Analysis of student housing choices indicates that proximity to campus, affordable rent, and adequate facilities are the main factors in their decisions. Strategic location, close to infrastructure and easy access, as well as facilities like kitchens and parking spaces, are highly valued. Security features, such as CCTV and guards, and environmental comfort are also additional considerations, while boarding houses far from activity centers, expensive, or overly exclusive are less popular. In conclusion, students tend to seek housing that offers the best combination of location, price, facilities, security, and comfort to efficiently support their daily lives.